Cryptosporidium infecting wild cricetid rodents from the subfamilies Arvicolinae and Neotominae - Stenger, Brianna L S; Horčičková, Michaela; Clark, Mark E; Kváč, Martin; Čondlová, Šárka; Khan, Eakalak; Widmer, Giovanni; Xiao, Lihua; Giddings, Catherine W; Pennil, Christopher; Stanko, Michal; Sak, Bohumil; et al. (Parasitology, 2018)
We undertook a study on Cryptosporidium spp. in wild cricetid rodents. Fecal samples were collected from meadow voles (Microtus pennsylvanicus), southern red-backed voles (Myodes gapperi), woodland voles (Microtus pinetorum), muskrats (Ondatra zibethicus) and Peromyscus spp. mice in North America, and from bank voles (Myodes glareolus) and common voles (Microtus arvalis) in Europe. Isolates were characterized by sequence and phylogenetic analyses of the small subunit ribosomal RNA (SSU) and actin genes. Overall, 33·2% (362/1089) of cricetids tested positive for Cryptosporidium, with a greater prevalence in cricetids from North America (50·7%; 302/596) than Europe (12·1%; 60/493). Principal Coordinate analysis separated SSU sequences into three major groups (G1-G3), each represented by sequences from North American and European cricetids. A maximum likelihood tree of SSU sequences had low bootstrap support and showed G1 to be more heterogeneous than G2 or G3. Actin and concatenated actin-SSU trees, which were better resolved and had higher bootstrap support than the SSU phylogeny, showed that closely related cricetid hosts in Europe and North America are infected with closely related Cryptosporidium genotypes. Cricetids were not major reservoirs of human pathogenic Cryptosporidium spp.
Keywords: hlodavci; Feces; zdroje nemoci; Genotype; fylogeneze; kryptosporidióza; Rodentia; Sequence Analysis, DNA; Cryptosporidiosis; Phylogeny; Animals, Wild; biogeography; Cricetidae; sekvenční analýza DNA; Europe; divoká zvířata; Phylogeography; RNA, Ribosomal; Evropa; phylogenetics; Animals; RNA ribozomální; zvířata; Disease Reservoirs; Arvicolinae; fylogeografie; myši; North America; Cryptosporidium; genotyp; Mice; feces; Severní Amerika